2022
DOI: 10.3390/s22135007
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Multimodal-Based Prognosis and Intervention Prediction Model for COVID-19 Patients in a Multicenter Cohort

Abstract: The ability to accurately predict the prognosis and intervention requirements for treating highly infectious diseases, such as COVID-19, can greatly support the effective management of patients, especially in resource-limited settings. The aim of the study is to develop and validate a multimodal artificial intelligence (AI) system using clinical findings, laboratory data and AI-interpreted features of chest X-rays (CXRs), and to predict the prognosis and the required interventions for patients diagnosed with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Similar results from other studies also elicited dyspnea as a significant clinical variable for mortality prediction among COVID-19 patients (31). A meta-analysis study by He et al showed that dyspnea was the main difference between mild and severe COVID-19 [40], and another study confirmed this observation (32).…”
Section: Serum Ferritin Has Been Cited As One Of the Mortality Indica...supporting
confidence: 66%
“…Similar results from other studies also elicited dyspnea as a significant clinical variable for mortality prediction among COVID-19 patients (31). A meta-analysis study by He et al showed that dyspnea was the main difference between mild and severe COVID-19 [40], and another study confirmed this observation (32).…”
Section: Serum Ferritin Has Been Cited As One Of the Mortality Indica...supporting
confidence: 66%
“…Several published reports have used deep learning of actual CXR images in combination with EMR data to predict the risk of intubation for patients admitted with COVID-19. Kwon et al [14], Aljouie et al [19], and Lee et al [39] used systematic manual scoring or manual labeling of CXR images to predict mechanical ventilation and deaths, achieving high performance; however, the utility of these approaches is limited, as it requires manual scoring by experts and cannot easily be rolled out to stressed health systems in an automated manner. Jiao et al [40] also used transfer learning on an ImageNet pretrained model to generate an image classifier used in fusion with EMR data to generate a classifier for intubation in patients with COVID-19 [40].…”
Section: Discussionmentioning
confidence: 99%